Study of different super-disintegrants and their use as a magic ingredient for different immediaterelease tablets (Journal of Pharmaceutical Negative Results, 2022)
The time taken by the tablet to break down into fragments or granules is called disintegration. The time it takes for a batch of tablets to dissolve into particles under certain circumstances is called a disintegration test. It essentially entails an aqueous liquid penetrating the tablet, disrupting internal bonds, and the tablet breaking down as a result. A gadget defined in the USP/NF is used to determine how long it requires a tablet to dissolve. The powder compact's disintegration and dissolution behavior have the greatest impact on a drug's performance. For immediate-release dose formulations, the breakdown process is very important.